Detection of the Diversity of Cytoplasmic Male Sterility Sources in Broccoli (Brassica Oleracea var. Italica) Using Mitochondrial Markers - Shu, Jinshuai; Liu, Yumei; Li, Zhansheng; Zhang, Lili; Fang, Zhiyuan; Yang, Limei; Zhuang, Mu; Zhang, Yangyong; Lv, Honghao (Frontiers in Plant Science, 2016)
Broccoli (Brassica oleracea var. italica) is an important commercial vegetable crop. As part of an efficient pollination system, cytoplasmic male sterility (CMS) has been widely used for broccoli hybrid production. Identifying the original sources of CMS in broccoli accessions has become an important part of broccoli breeding. In this study, the diversity of the CMS sources of 39 broccoli accessions, including 19 CMS lines and 20 hybrids, were analyzed using mitochondrial markers. All CMS accessions contained the ogu orf138-related DNA fragment and the key genes of nap CMS, pol CMS, and tour CMS were not detected. The 39 CMS accessions were divided into five groups using six orf138-related and two simple sequence repeat markers. We observed that ogu CMS R3 constituted 79.49% of the CMS sources. CMS6 and CMS26 were differentiated from the other accessions using a specific primer. CMS32 was distinguished from the other accessions based on a 78-nucleotide deletion at the same locus as the orf138-related sequence. When the coefficient was about 0.90, five CMS accessions (13CMS6, 13CMS23, 13CMS24, 13CMS37, and 13CMS39) exhibiting abnormal floral organs with poor seed setting were grouped together. The polymerase chain reaction amplification profiles for these five accessions differed from those of the other accessions. We identified eight useful molecular markers that can be used to detect CMS types during broccoli breeding. Our data also provide important information relevant to future studies on the possible origins and molecular mechanisms of CMS in broccoli.